Uma introdução às equações de diferenças. - Calado, Ivone Maria Gonçalves (2013)
Nem sempre se atribuiu às Equações de Diferenças a importância que hoje se lhes dá. Foi necessário que aparecesse o computador digital para que elas adquirissem o seu real valor e grande relevo no contexto actual da Matemática. Sucintamente, e em traços largos, vou apresentar a composição deste trabalho. No capítulo um são apresentados alguns pré-requisitos que irão ser necessários no desenvolvimento deste tema, tais como o conceito de sucessão, relação de recorrência e algoritmo recursivo. As taxas de juro composto e o número de movimentos da Torre de Hanói são exemplos, que usam algoritmos recursivos. As equações de diferenças dividem-se em dois grandes grupos: lineares e não lineares. Todo o capítulo dois é dedicado às equações de diferenças lineares, homogéneas e não homogéneas, sendo desenvolvido neste capítulo vários métodos de resolução. No capítulo três é definido o conceito de ponto fixo e determinam-se graficamente as soluções das equações de diferenças, usando o método da Teia de Aranha. Este método serve como base ao estudo das equações de diferenças não lineares. É vastíssimo o campo das equações de diferenças não lineares, no capítulo quatro é estudado com todo o pormenor, a equação de diferenças logística. Por fim são dadas várias aplicações das equações de diferenças, nas mais diversas áreas, tais como, não podia deixar de ser, na Matemática, na Economia, em estratégias de guerra, na Física e nos estudos da variação das populações. Difference Equations have not always been treated with the importance they are given today. It has taken the emergence of the digital computer to show their true worth and great importance in present day Mathematics. This work is broadly structured as follows. Chapter one deals with some prerequisites for the development of the topic, such as the concept of succession, the recurrence relation and recursive algorithms. Compound interest rates and the number of moves in the Hanói Tower puzzle are instances that use recursive algorithms. Difference equations can be divided into two major groups: linear and nonlinear. Chapter two concerns linear difference equations, both homogeneous and nonhomogeneous, and describes various methods to resolve them. The fixed point theory is tackled in Chapter three, and solutions of difference equations are determined graphically, using the Cobweb method. This method is the basis for the study of nonlinear difference equations. The field of nonlinear difference equations is immense, and Chapter four examines the logistic difference equation. Finally, examples are given of the many applications of difference equations, and a wide variety of areas such as Mathematics (naturally), Economics, war strategy, Physics and the study of population change.Difference Equations have not always been treated with the importance they are given today. It has taken the emergence of the digital computer to show their true worth and great importance in present day Mathematics. This work is broadly structured as follows. Chapter one deals with some prerequisites for the development of the topic, such as the concept of succession, the recurrence relation and recursive algorithms. Compound interest rates and the number of moves in the Hanói Tower puzzle are instances that use recursive algorithms. Difference equations can be divided into two major groups: linear and nonlinear. Chapter two concerns linear difference equations, both homogeneous and nonhomogeneous, and describes various methods to resolve them. The fixed point theory is tackled in Chapter three, and solutions of difference equations are determined graphically, using the Cobweb method. This method is the basis for the study of nonlinear difference equations. The field of nonlinear difference equations is immense, and Chapter four examines the logistic difference equation. Finally, examples are given of the many applications of difference equations, and a wide variety of areas such as Mathematics (naturally), Economics, war strategy, Physics and the study of population change.